Treatment outcome of hepatolithiasis: Nepalese experience - Pandit, Narendra; Awale, Laligen; Yadav, Tek Narayan; Deo, Kunal Bikram; Adhikary, Shailesh (International Surgery Journal, 2020)
Background: Hepatolithiasis is a rare disease with high rate of treatment failure and recurrence. This study aims to review the burden, management and outcome from an endemic region. Methods: A retrospective review of database of patients with hepatolithiasis managed surgically from 2015 to 2019 was performed. Diagnosis was based on the clinical findings and radiological investigations. Demographic data, clinical presentation, extent of disease and type of surgical management were evaluated. The outcome measures included immediate stone clearance, postoperative complications and follow-up. Results: Hepatolithiasis was seen in nine (0.34%) out of 2,600 patients being evaluated for gallstone disease. Three patients were young, while the remaining six were in the middle-age group. The presenting symptoms were pain abdomen (78%) and jaundice (22%). Hepatolithiasis was located in the left, right and both ductal systems in 5, 1 and 3 patients respectively. Liver resection for unilateral disease was done in 3 patients: left hepatectomy (n=2) and left lateral segmentectomy (n=1). High bile duct exploration and bilio-enteric drainage was done in 5 patients. One patient required hepatolithotomy and T-tube drainage due to cholangitis. Complete stone clearance was achieved in 78%. Complications included surgical site infection and cholangitis in 2 patients. There was no operative mortality. Histopathology revealed recurrent pyogenic cholangitis. At median follow-up of 28 months, 7 patients are symptom-free. Conclusions: Hepatectomy is an effective treatment when disease is confined to the left lobe. Combined surgical procedure is an acceptable option for bilateral or right-sided hepatolithiasis.